The Birth of Information in the Brain: Edgar Adrian and the Vacuum Tube. Issue 1 (9th February 2015) - Garson, Justin
Argument: As historian Henning Schmidgen notes, the scientific study of the nervous system would have been "unthinkable" without the industrialization of communication in the 1830s. Historians have investigated extensively the way nerve physiologists have borrowed concepts and tools from the field of communications, particularly regarding the nineteenth-century work of figures like Helmholtz and in the American Cold War Era. The following focuses specifically on the interwar research of the Cambridge physiologist Edgar Douglas Adrian, and on the technology that led to his Nobel-Prize-winning research, the thermionic vacuum tube. Many countries used the vacuum tube during the war for the purpose of amplifying and intercepting coded messages. These events provided a context for Adrian's evolving understanding of the nerve fiber in the 1920s. In particular, they provide the background for Adrian's transition around 1926 to describing the nerve impulse in terms of "information, " "messages, " "signals, " or even "codes, " and for translating the basic principles of the nerve, such as the all-or-none principle and adaptation, into such an "informational" context. The following also places Adrian's research in the broader context of the changing relationship between science and technology, and between physics and physiology, in the first few decades of the twentieth century.